The Responsive Needs Tool – unlocking communication of end of life care needs. Issue 2 (1st June 2012) - Ball, B.; Johnson, B.; Bake, J.
Abstract : Introduction: The Lincolnshire Home Deaths Project Group brought together organisations from across the county to develop new ways of working that were patient focussed and to ensure that end of life services dovetailed. This included a night care pilot which identified the need for an assessment and communication tool endorsed by the health and social care community to enable the needs led prioritisation of resource in end of life care. Aims and Methods: To enable clear, accurate and effective communication of need across organisations to support the allocation and re-allocation of available night care resources for patients at the end of life based on their clinical need. The 'responsive need' tool was devised by members of the group using the work of two organisations, Marie Curie Cancer Care and St Barnabas Lincolnshire Hospice and the Gold Standards prognostic indicators as a resource. Results: The tool has become the common 'currency' of communication countywide and is incorporated into SystmOne palliative care template. It has enabled the provision of end of life care according to need, and stopped unmet need for complex patients in the pilot area. Given clinicians confidence that the care will be there when the patient needs it; releasing care and supporting new ways of working. Conclusion: The responsive need tool has supported choice at the end of life for patients and would be of interest to both those commissioning and providing end of life care.